Penafsiran Masa Sahabat, Di antara Perbedaan Pemahaman dan Perpecahan Umat. - Sadewa, Mohammad Aristo (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThis paper aims to trace the history of the development of interpretation in the time of the Companions. This research uses a comparative-descriptive method with a qualitative approach. So it can be concluded that the development of the interpretation of the Companions period cannot be separated from the different conditions of the Companions in understanding the Qur'an. In addition, at that time there was also a division among the friends. The differences in understanding and division of the people have implications for the interpretation carried out. Differences in understanding do not have such a big impact, while the division of the ummah has a very big impact on interpretation. The division of the ummah which resulted in the emergence of distorted interpretations under the pretext of justifying their sect. The sources of interpretation carried out are the Qur'an, Hadith, Ijtihad, and Ahl-Kitab. AbstrakTulisan ini bertujuan untuk melacak sejarah perkembangan tafsir di masa sahabat. Penelitian ini menggunakan metode komparatif-deskriptif dengan pendekatan kulitatif. Sehingga dapat disimpulkan bahwa perkembangan penafsiran masa sahabat tidak terlepas dari kondisi sahabat yang berbeda dalam memahami al-Qur’an. Ditambah lagi pada saat itu muncul juga sebuah perpecahan di antara para sahabat. Dari perbedaan pemahaman dan perpecahan umat tersebut berimplikasi kepada penafsiran yang dilakukan. Perbedaan pemahaman tidak berdampak begitu besar, sedangkan perpecahan umat dampaknya begitu besar bagi penafsiran. Perpecahan umat yang mengakibatkan munculnya penafsiran yang menyeleweng dengan dalih untuk menjustifikasi alirannya. Sumber-sumber penafsiran yang dilakukan ialah dengan al-Qur’an, Hadits, Ijtihad, dan Ahl-Kitab. Kata Kunci: Perbedaan Pemahaman; Perpecahan Umat; Tafsir Sahabat.